2015
DOI: 10.1080/00949655.2015.1022781
|View full text |Cite
|
Sign up to set email alerts
|

A flexible sampling scheme for variables inspection with loss consideration

Abstract: This article develops a variables sampling scheme for resubmitted lots by incorporating the concept of Taguchi loss function. The probability of lot acceptance is derived based on the exact sampling distribution and two-point condition on operating characteristic curve is used to determine the plan parameters that meet both the producer's and consumer's quality and risk requirements. Moreover, the performance of the proposed variables resubmitted sampling plan is investigated and compared with the classical va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Wu 13 investigated the coverage rates of the generalized confidence intervals on the basis of the C pm index with the consideration of measurement errors and performed a sensitivity analysis on the confidence interval performance. Recently, Wu et al 14 incorporated the concept of a Taguchi loss function to develop a variable sampling scheme for resubmitting lots and presented that the new method needs less times of inspection has less inspection under certain conditions. Liao 15 compared the estimators of C pm by the Markov Chain Monte Carlo and bootstrap techniques, and the simulation results indicated that the former performed better in most cases.…”
Section: Loss‐based Index Cpmmentioning
confidence: 99%
“…Wu 13 investigated the coverage rates of the generalized confidence intervals on the basis of the C pm index with the consideration of measurement errors and performed a sensitivity analysis on the confidence interval performance. Recently, Wu et al 14 incorporated the concept of a Taguchi loss function to develop a variable sampling scheme for resubmitting lots and presented that the new method needs less times of inspection has less inspection under certain conditions. Liao 15 compared the estimators of C pm by the Markov Chain Monte Carlo and bootstrap techniques, and the simulation results indicated that the former performed better in most cases.…”
Section: Loss‐based Index Cpmmentioning
confidence: 99%